Resonant scattering of green light enabled by Ag@TiO2 and its application in a green light projection screen - Ye, Yiyang (2019)
The ability to selectively scatter green light is essential for an RGB transparent projection display, and this can be achieved by a silver-core, titania-shell nanostructure (Ag@TiO2), based on the metallic nanoparticle's localized surface plasmon resonance. The ability to selectively scatter green light is shown in a theoretical design, in which structural optimization is included, and is then experimentally verified by characterization of a transparent film produced by dispersing such nanoparticles in a polymer matrix. A visual assessesment indicates that a high-quality green image can be clearly displayed on the transparent film. For completeness, a theoretical design for selective scattering of red light based on Ag@TiO2 is also shown.